The Practical Method of Understanding Hadith Based on Ali Mustafa Yaqub - Hasan Su'aidi; Moh. Erfan Soebahar; A. Hassan Asy’ari Ulama’i (Religia, 2022)
Hadith as a source of law other than the Qur'an obtains a very large portion of attention from Muslims. This is because the hadith has several functions in the Qur'an, such as bayÄn tafsr, bayÄ«Än tasyrÄ«', and bayÄn taukÄ«d. Many scientific tools are needed before implementing them in daily life. The analysis of the authenticity of the hadith, both sanad and matan, is the first thing that must be conducted before understanding the contents. Yet, it does not mean that understanding the hadith is not important compared to determining the authenticity of the hadith. Because the issue of the authenticity of the hadith has been carried out since the process of transmitting the hadith. It is different from the understanding of hadith which has developed recently and continues to have dynamics. Hadith observers have offered many methods of understanding hadith, both textual and contextual. However, along with the development of science, the method is also developing, such as the use of various scientific approaches, including social sciences to study the meaning of hadith. This is like the method offered by Ali Mustafa Yaqub which includes a cultural, social and geographical approach. This paper attempted to analyze the practical steps of the hadith understanding method offered by Ali Mustafa Yaqub in his book al-á¹¬uruq al-á¹¢aá¸¥Ä«á¸¥ah FÄ« Fahmi al-Sunnah al-Nabawiyyah